ديو البحرية 915 هـ. = 1509 م. وأثرها في إنهيار دولة سلاطين المماليك: دراسة تحليلية - عبدالعظيم، إيمان مصطفى; محمد، طارق أبو الوفا (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2021)
ديو اسم لبلدة في مقاطعة هندية موجودة للآن، على أرضها قامت معركة بحرية شهيرة، بين طرفين دوليين هما: سلاطين المماليك "سلاطين مصر والشام" وقتئذ، والبرتغال، إحدى قوى أوروبا في القرن السادس عشر الميلادي/ التاسع الهجري، وهي ذات الموقعة التي حسمت الصراع بين الشرق والغرب الأوربي الدائر حول السيطرة على طرق التجارة الشرقية الواردة لأوروبا، وعن الأسباب التي دفعت للصدام الحربي بين هذين الطرفين، وكيف كان؟ وما هي أحداثه؟ وكيف انتهي؟ وما هي نتائجه؟، ستدور هذه الورقة البحثية، في محاولة لكشف الغموض عن هذه الفترة الزمنية، وطبيعة العلاقات السياسية بين الشرق والغرب الأوربي وقتئذ، من خلال عدة نقاط رئيسة، منها: ديو بين الجغرافيا والتاريخ، أسباب وقوع المعركة، وأحداثها، ونتائجها، ثم نختتم بذكر أهم ما وصلت إليه الدراسة من نتائج، وكيف كان أثر هذه العركة البحرية فاصلا وحاسما في تداعي سلطنة دولة المماليك، وزوال سيطرتها البحرية "سلطة ونفوذ" على خطوط التجارة البحرية بين الشرق الإسلامي والغرب الأوروبي.
Diu is a name for a town in an Indian province that exists so far, on its soil a famous naval battle took place, between two international parties: the Mamluk sultans, “the sultans of Egypt and al- sham” at that time, and Portugal, one of the powers of Europe in the sixteenth century AD / ninth century AH, which is the same location that settled the conflict Between East and West European revolving around control of eastern trade routes imported to Europe, and about the reasons that prompted the war clash between these two parties, and how was it? What are its events? How did it end? What are its results? This research paper will revolve, in an attempt to reveal the ambiguity of this time period, and the nature of political relations between East and Western Europe at the time, through several key points, including: a dew between geography and history, the causes of the battle, its events, and its results, then we conclude by mentioning the most important The study has some results, and how was the impact of this maritime battle a decisive and decisive factor in the decline of the Mamluk Sultanate, and the disappearance of its maritime control, "authority and influence" on the maritime trade lines between the Islamic East and the European West. We hope that Allah will grant us success, and continue research studies in the field of Mamluk era. God grants success
Keywords: التجارة البحرية -- سلاطين المماليك -- البرتغال -- الحروب -- ديو، الهند